Evaluation of Non-Tender Services in the Procurement of Goods and Services in the Goods/Services Procurement Services Section of Andalas University Hospital - Zahra, Siti; Syamsir, Syamsir (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2024)
This research aims to evaluate non-tender services in the procurement of goods and services in the Goods/Services Procurement Services Section of Andalas University Hospital. This research was conducted at the Andalas University Hospital, with data collected and processed through interviews, document studies, and observations using qualitative analysis techniques and descriptive methods. The results of this research show that the evaluation was carried out on Reliability, Responsiveness, Guarantee, Empathy and Physical Evidence. Evaluation of the quality of non-tender services in the procurement of goods and services at Andalas University Hospital revealed strengths in the dimensions of reliability and physical evidence, but showed the need for improvement in responsiveness, assurance and empathy. Obstacles in non-tender services in the procurement of goods and services in the goods/services procurement service section of Andalas University Hospital are miscommunication, budget limitations, uncertainty about payment times, high workload are factors that influence the efficiency and effectiveness of the procurement process. Efforts in non-tender services in the procurement of goods and services in the goods/services procurement services section of Andalas University Hospital include conducting in-depth and periodic evaluations, conducting training and technical guidance, improving communication and coordination between units, optimizing budget management, more efficient payment management. Improved Administrative Procedures and Work Efficiency, Improved Quality and Cleanliness of Goods Received.